(3cJGH GdTjhYs - (3GdMfaj GdNQGSGfj, CHh eMeO, GdnqUrOQ GdnqTpgjO, HQgGf GdCFeI, YeQ Hf YHO GdYRjR Hf YeQ Hf eGRI, (B536 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddN hMOg hHYO ajbhd GdEeGe GdCLd MSGe GdOjf JaUjd eG GNJda aj eSGFd GdTjhY heG GJab Ydjg aGdcdGe aj eYQaI eSGFd GdTjhY aj CQHYI aUhd s
(3BNQgG (B:s
(3hgh JCbjJ GdYbO hjSJhj GdLhGH aj GdbSejf hgh GdTGjY GdPj jMJed GdbSeI hGdTGjY GdPj dG jMJed GdbSeI dGf eG gh (B( (3cPG (B) (3GdeGfY jTJed GdbSejf hgh JCbjJ GdYbO s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5 / 51s
(3eYLe GdeDdajf (B2 / 562s
(3cTa GdXfhf (B2 / 1431s
(3GdLhGgQ GdeVjI (B1 / 391s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs